2021
DOI: 10.1167/iovs.62.10.7
|View full text |Cite
|
Sign up to set email alerts
|

Fine Particulate Matter and Age-Related Eye Disease: The Canadian Longitudinal Study on Aging

Abstract: Purpose To determine the relationship between fine particulate matter (PM 2.5 ) and ocular outcomes such as visual impairment and age-related eye disease. Methods Baseline data were used from the Canadian Longitudinal Study on Aging. The Comprehensive Cohort consisted of 30,097 adults ages 45 to 85 years. Annual mean PM 2.5 levels (µg/m 3 ) for each participant's postal code were estimated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 38 publications
3
49
0
Order By: Relevance
“…There was no increased risk of cataract reported for those with greater exposure to PM 2.5 . Finally, Grant et al 24 reported a borderline association between PM 2.5 and cataract (OR = 1.06 per IQR; 95% CI, 0.99–1.14) in a single-pollutant model. However, they did not find an increased odds of cataract among those with greater exposure levels to PM 2.5 (OR = 0.98 per IQR; 95% CI, 0.90–1.07) in the multipollutant model.…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…There was no increased risk of cataract reported for those with greater exposure to PM 2.5 . Finally, Grant et al 24 reported a borderline association between PM 2.5 and cataract (OR = 1.06 per IQR; 95% CI, 0.99–1.14) in a single-pollutant model. However, they did not find an increased odds of cataract among those with greater exposure levels to PM 2.5 (OR = 0.98 per IQR; 95% CI, 0.90–1.07) in the multipollutant model.…”
Section: Resultsmentioning
confidence: 95%
“…Chua et al 22 did not present a multipollutant model. Third, Grant et al 24 reported that those who lived in areas with higher PM 2.5 levels were more likely to have visually impairing AMD (OR = 1.51 per IQR; 95% CI, 1.10–2.08) in a single–pollutant model. However, in a multipollutant model, they found a borderline association between exposure to PM 2.5 and visually impairing AMD (OR = 1.41 per IQR; 95% CI, 0.96–2.08).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations